The International Comparison of the Educational Systems of Iran, Myanmar and Ethiopia - Aye, Su Hnin; Agezew, Birhanu Haile; Iranfar, Arshia; Kovács, Karolina Eszter (Central European Journal of Educational Research, 2023)
Education systems usually fall into two main types: the Continental and Atlantic systems of education. Countries belonging to the third world often follow after the characteristics of the continental system, however, the specificities of the country may overwrite some characteristics of the original concept. This article aims to introduce some specific aspects of the educational systems of Iran, Ethiopia and Myanmar through the comparison of these systems. According to the data analysis, centralisation is relevant, but decentralisation tends to be strengthened in each country. Concerning their structure, similarities in the division of levels were identified, along with differences in duration and focus. Unsurprisingly, the curriculums are different in each country; however, the basic subjects are almost the same. Finally, the grading systems use similar categories, although the underlying points providing the basis for the grades significantly differ. Comparing them can contribute to their evaluation and further development.